Pedagogía de la propiocepción corporal en el cantante: Un estudio exploratorio en estudiantes universitarios. (2020)
This article, which derived from the research project New pedagogies in the teaching of singing in the formative context of the School of Arts and Music of the Sergio Arboleda University, aimed to investigate proprioceptive mechanisms and the degrees of internal awareness developed by singers in training within a collective learning expe-rience was. The results, analyzed from a hermeneutic position, expose the reflections, dilemmas and achievements originated in the process of construction of one’s corpo-reality and the different adjustments and perceptive developments for an adequate articulation between the voice and the body. The conclusions highlight the importance of proprioception as social and intersubjective learning through an internalization process in which the singer’s subjectivity to express their inner world is valued.